Compositional variations in algal organic matter during distinct growth phases in karst water - Tian, Liye; Zhang, Zhiwei; Wang, Zhikang; Zhang, Ping; Xiong, Chao; Kuang, Ye; Peng, Xingyi; Yu, Mengxin; Qian, Yu (Frontiers in Environmental Science, 2023)
Inland surface water plays an important role in global carbon cycling, which responds to transformation between dissolved inorganic carbon (DIC) and dissolved organic carbon (DOC). Studies have shown that algae in karst lakes and reservoirs can convert DIC to organic matter (OM) and form a stable carbon sink via photosynthesis. However, pathways of conversion from inorganic carbon to organic carbon within the algae growth remains unclear and needs further investigation. In this study, spectroscopic techniques were applied to investigate the variations of algae organic matter (AOM) composition in growth metabolism of Chlorella vulgaris and Scenedesmus obliquus in simulated karst water condition. The results showed that extracellular organic matter (EOM) of algae contained a high DIC concentration during the adaptation phase, which ensured the carbon source for photosynthesis of algae. In addition, DOC in algae increased after entering stationary phase, while more OM was released into water. With algae growth proceeds, amino structural material in EOM was consumed to produce more aromatic protein-like material, while more lipid material was produced in intracellular organic matter (IOM). The spectral characterization results could intuitively determine AOM dynamics in different growth stages of algae, which favored for establishing effective and predictable approaches for organic carbon variations, as well as respond to regional carbon cycling in karst water.